A hard place to call home: a Canadian perspective on residential care and treatment for children and youth - Gharabaghi, Kiaras (Canadian Scholars, 2019)
"Dial Tone" / Cory MacKinlay -- The Problem of Translation -- The Voices of Young People -- Theoretical Foundations of Residential Care and Treatment in Canada -- Practice-Based Evidence for Excellence -- Institutional and Everyday Cultures -- Aesthetic and Sensory Contexts -- Beyond the Plan of Care -- The Lived Experience of Staff -- Networked Practices -- Residential Care and Treatment in the Context of Systems -- Redesigning the Professional Landscapes for Residential Care and Treatment in Canada -- The Case for a Democratic System of Care.